PERAN CSE DALAM MEMODERASI PENGARUH COMPUTER KNOWLEDGE, MOTIVASI BELAJAR, FASILITAS LABORATORIUM TERHADAP HASIL BELAJAR SPREADSHEET - Ramadhani, Aisyah Putri; Bahtiar, Moh Danang (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research aims to determine the influence of computer knowledge, learning motivation, and laboratory facilities on learning outcomes in spreadsheet material with computer self-efficacy as a moderating variable. The population in this study was class X AKL students at SMKN 1 Kemlagi for the 2023/2024 academic year, totaling 107 students. The sample used was 84 students selected using simple random sampling techniques. Hypothesis testing uses the F Test, T Test and MRA Test. The research results show that (1) computer knowledge has a positive and significant effect on learning outcomes in spreadsheet material; (2) learning motivation does not have a positive and significant effect on learning outcomes in spreadsheet material; (3) laboratory facilities do not have a positive and significant effect on learning outcomes in spreadsheet material; (4) computer self-efficacy cannot moderate the influence of computer knowledge on learning outcomes in spreadsheet material; (5) computer self-efficacy cannot moderate the influence of learning motivation on learning outcomes in spreadsheet material; (6) computer self-efficacy cannot moderate the influence of laboratory facilities on learning outcomes in spreadsheet material.